Development of a Framework for Emergency Risk Reduction in Android-Based Agriculture Areas (E'nurse App During the Covid-19 Pandemic) - Musviro Musviro; Suhari; P.M Rahmawati; Anggia Astuti (KHD-Production, 2021)
Introduction: Covid-19 has now been declared a pandemic case, the agricultural sector is no exception. Farmers' health during the Covid-19 pandemic and the high risk of emergencies and disasters in agricultural areas need solutions in handling efforts. Purpose: developing a framework for reducing the risk of emergencies and disasters in agricultural areas based on android (E'Nurse App during the Covid-19 pandemic) by compiling the design of the E'Nurse App and analyzing the effect of the E'Nurse App on farmers' understanding in reducing the risk of emergencies and disasters in areas agriculture. Method: a mix of qualitative methods with an interpretive phenomenology approach to design the E'Nurse App (Emergensy Nursing) application, followed by quantitative methods with the Spearman Rho test and a questionnaire measuring tool. Respondents in this study were farmers of Pandalungan. Result: Formed the design of the E'Nurse App application, the pre-post treatment test obtained the value of r = 0.678,> α = 0.05. This means that there is an effect of providing education through the smart app application on farmers' understanding in reducing the risk of emergencies and disasters in agricultural areas with a strong relationship. Conclusion: The E'Nurse App affects farmers' understanding in reducing the risk of emergencies and disasters in agricultural areas during the Covid-19 pandemic.